Anti-Dissipative Strategies toward More Efficient Solar Energy Conversion - Troian-Gautier, Ludovic; Cadranel, Alejandro; Cotic, Agustina; Cerfontaine, Simon; Slep, Leonardo D.; Elias, Benjamin (Journal of the American Chemical Society, 2023)
In natural and artificial photosynthesis, light absorption and catalysis are separate processes linked together by exergonic electron transfer. This leads to free energy losses between the initial excited state, formed after light absorption, and the active catalyst formed after the electron transfer cascade. Additional deleterious processes, such as internal conversion (IC) and vibrational relaxation (VR), also dissipate as much as 20-30% of the absorbed photon energy. Minimization of these energy losses, a holy grail in solar energy conversion and solar fuel production, is a challenging task because excited states are usually strongly coupled which results in negligible kinetic barriers and very fast dissipation. Here, we show that topological control of oligomeric Ru(bpy)3 chromophores resulted in small excited-state electronic couplings, leading to activation barriers for IC by means of inter-ligand electron transfer of around 2000 cm-1 and effectively slowing down dissipation. Two types of excited states are populated upon visible light excitation, that is, a bridging-ligand centered metal-to-ligand charge transfer [MLCT(Lm)], and a 2,2 '-bipyridine-centered MLCT [MLCT(bpy)], which lies 800-1400 cm-1 higher in energy. As a proof-of-concept, bimolecular electron transfer with tri-tolylamine (TTA) as electron donor was performed, which mimics catalyst activation by sacrificial electron donors in typical photocatalytic schemes. Both excited states were efficiently quenched by TTA. Hence, this novel strategy allows to trap higher energy excited states before IC and VR set in, saving between 100 and 170 meV. Furthermore, transient absorption spectroscopy suggests that electron transfer reactions with TTA produced the corresponding Lm center dot–centered and bpy center dot–centered reduced photosensitizers, which involve different reducing abilities, that is, -0.79 and -0.93 V versus NHE for Lm center dot-and bpy center dot-, respectively. Thus, this approach probably leads in fine to a 140 meV more potent reductant for energy conversion schemes and solar fuel production. These results lay the first stone for anti-dissipative energy conversion schemes which, in bimolecular electron transfer reactions, harness the excess energy saved by controlling dissipative conversion pathways.
CRIS-Team WoS Importer:2023-03-17